KAJIAN HUKUM ISLAM PERSPEKTIF ORIENTALISME - Masse, Rahman Ambo (DIKTUM: Jurnal Syariah dan Hukum, 2014)
The study of Islamic law has always been an interesting discourse to be discussed. Especially when Islamic law used as feedstock national legislation. Indonesian Islamic law reformers among the developing discourse that gave birth to the two groups with the character and tendency of thought is diametrically different. The first group, discuss the application of Islamic law with legalistic -textual approach, namely that Islamic law should be applied textually and enforced for all Indonesian Muslims . Islamic law - textual legally in Indonesia can be realized if supported by political struggle. Civic groups voiced discourse, among others, is Hizbur Tahrir Indonesia (HTI), and the Islamic Defenders Front (FPI). This group tends to struggle line radical - conservative by means of dialogue and anarchism combines street parliament. The second group, using substantial - cultural approach, namely that Islamic law does not need to be formalized in the form of legislation, but the most important is the absorption of Islamic values in the socio-cultural life of Indonesian Muslims. Acculturation Islamic values, such as honesty, liberty, justice, and equality before the law needs to be actualised in the daily life of Indonesian Muslim society is far more important than the formalization of the religious teachings . This group is represented by the Liberal Islam Network.